Fabrication of poly (diallyldimethylammonium chloride) (PDDA) functionalized multi-walled carbon nanotubes paper electrode for simultaneous detection of dopamine and ascorbic acid - Pui, Tze-Sian (2020)
A paper-based electrode based on nanocomposite, comprising of carboxylated multi-walled carbon nanotubes (MWNTs) and poly (diallyldimethylammonium chloride) (PDDA), has been successfully developed for simultaneous detection of dopamine (DA) and ascorbic acid (AA) in 0.1 M phosphate buffer solution (PBS). The fabrication of PDDA/MWNTs electrodes involves two steps: PDDA absorbed onto the surface of carboxylated MWNTs and drop-casting the aqueous mixture of PDDA/MWNTs onto the paper. The electrode size was defined by a window cut into a laminating film. Differential pulse voltammetry was performed with DA concentration ranging from 2 μM to 500 μM in the presence of 1mM AA. On the surface of PDDA/MWNTs electrode, DA and AA were oxidized respectively at distinguishable potential of 0.156 and -0.068 V (vs. Ag/AgCl). The detection limit of DA was estimated to be 0.8 μM. This nanocomposite electrode has potential application in bioanalysis and biomedicine.